2008
DOI: 10.1038/nchembio.86
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the endocannabinoid system by organophosphorus nerve agents

Abstract: Delta(9)-tetrahydrocannabinol (THC), the psychoactive ingredient of marijuana, has useful medicinal properties but also undesirable side effects. The brain receptor for THC, CB(1), is also activated by the endogenous cannabinoids anandamide and 2-arachidonylglycerol (2-AG). Augmentation of endocannabinoid signaling by blockade of their metabolism may offer a more selective pharmacological approach compared with CB(1) agonists. Consistent with this premise, inhibitors of the anandamide-degrading enzyme fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
124
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 41 publications
9
124
1
Order By: Relevance
“…Although hepatic CB1 activation probably is the target of our observed effects, we cannot exclude centrally mediated actions upon peripheral tissues because brain EC levels are elevated as well (18). However, the ablation of TG elevation in apoEϪ/Ϫ mice even in the presence of full-blown cannabinoid behavioral effects (observed in this study in IDFPtreated apoEϩ/ϩ and Ϫ/Ϫ mice and ref.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Although hepatic CB1 activation probably is the target of our observed effects, we cannot exclude centrally mediated actions upon peripheral tissues because brain EC levels are elevated as well (18). However, the ablation of TG elevation in apoEϪ/Ϫ mice even in the presence of full-blown cannabinoid behavioral effects (observed in this study in IDFPtreated apoEϩ/ϩ and Ϫ/Ϫ mice and ref.…”
Section: Discussionmentioning
confidence: 68%
“…However, the ablation of TG elevation in apoEϪ/Ϫ mice even in the presence of full-blown cannabinoid behavioral effects (observed in this study in IDFPtreated apoEϩ/ϩ and Ϫ/Ϫ mice and ref. 18) strongly argues that the CB1-mediated hypertriglyceridemia and apoE effects are mediated peripherally. The development of peripheral CB1 antagonists that do not cross the blood-brain barrier and tissue-specific CB1Ϫ/Ϫ mouse models (13) will aid in addressing this issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, it has been found that organophosphorus nerve agents activate the endocannabinoid system inhibiting both enzymes FAAH and MAGL [9]. Arachidonic acid levels are decreased by the organophosphorus agents in amounts equivalent to elevations in 2-AG, which suggests that eicosanoid and endocannabinoid signalling pathways could co-ordinately regulated in the brain.…”
mentioning
confidence: 99%